Cost-effectiveness analysis of sugemalimab combined with chemotherapy as first-line treatment for advanced gastric cancer - Tang, Lian; Zhu, LongXun; Zhan, ShaoQing; Chen, Yong; Feng, Pan-Feng (Frontiers in Public Health, 2025)
ObjectiveBased on findings from the GEMSTONE-303 trial, the sugemalimab plus capecitabine and oxaliplatin regimen showed superior clinical efficacy compared to chemotherapy alone in advanced gastric cancer patients. This economic evaluation study assesses the cost-effectiveness of sugemalimab combination therapy within China’s healthcare system framework.MethodsA partitioned survival model was constructed based on data from the GEMSTONE-303 study, with a cycle length of 3 weeks. The model simulated patients’ direct medical costs and quality-adjusted life years (QALYs) over a 10-year period. The incremental cost-effectiveness ratio (ICER) was used as the evaluation metric, comparing the ICER against the willingness-to-pay (WTP) threshold (3 times China’s per capita GDP in 2024, 287,391 CNY/QALY). One-way sensitivity analysis and probabilistic sensitivity analysis were conducted to assess the robustness of the results.ResultsThe base-case analysis showed that the sugemalimab regimen provided greater health benefits compared to the placebo group (1.36 QALYs vs. 1.24 QALYs) but incurred significantly higher costs (271,041.24 CNY vs. 44,174.69 CNY), yielding an ICER of 1,890,554.58 CNY/QALY. One-way sensitivity analysis indicated that the utility values for the progressive disease (PD) state, progression-free survival (PFS) state, and the cost of sugemalimab had the most substantial impact on the ICER. Probabilistic sensitivity analysis demonstrated stable results, with a 0% probability that the sugemalimab combination regimen was cost-effective.ConclusionUnder the current economic conditions in China, sugemalimab combined with chemotherapy as a first-line treatment for advanced gastric cancer is not cost-effective.